2018
DOI: 10.1177/1120700017752565
|View full text |Cite
|
Sign up to set email alerts
|

Preservation technique of the piriformis tendon is superior to reattachment technique in terms of contiguity and muscle atrophy: using magnetic resonance imaging

Abstract: In our study, we suggest that the preservation technique of the piriformis tendon is superior to the reattachment technique in terms of contiguity and muscle atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, once the capsule and short external rotator muscles are resected, the re-rupture rate is high (75–92%), even if being repaired [ 23 , 24 ]. Previous reports have described modifications to surgical procedures performed to reduce the incidence of postoperative dislocations after hemiarthroplasty or THA with a posterior approach [ 13 , 14 , 25 , 26 ]. The CPP approach in BHA for femoral neck fractures preserves the attachment of short external rotator muscles; the dislocation rate was reported as 0% [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once the capsule and short external rotator muscles are resected, the re-rupture rate is high (75–92%), even if being repaired [ 23 , 24 ]. Previous reports have described modifications to surgical procedures performed to reduce the incidence of postoperative dislocations after hemiarthroplasty or THA with a posterior approach [ 13 , 14 , 25 , 26 ]. The CPP approach in BHA for femoral neck fractures preserves the attachment of short external rotator muscles; the dislocation rate was reported as 0% [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preserving soft tissue is important to reduce the risk of postoperative dislocation. Regarding contiguity, muscle atrophy, and dislocation, the piriformis tendon preservation strategy used during the posterior approach in total hip arthroplasty (THA) is said to be superior to the reattachment technique [ 13 ]. An external rotator preservation (ERP) procedure for THA described by Kim et al preserves muscles from the piriformis to the internal obturator muscle and has good outcomes with no cases of postoperative dislocation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The iliotibial band and quadratus femoris preservation, the smaller incision, the SERs and capsule repair [ 2 , 8 , 9 ], the surgeon’s seniority, physiotherapy and postoperative pain management protocols may have contributed to the early functional recovery of both groups; however, these parameters were similar between groups and cannot be considered responsible for their different outcomes. A recent posterior approaches’ comparative study found that the PF muscle demonstrated significantly less contiguity, atrophy and better function in patients where the PF was preserved than in those where PF was reattached [ 10 ]. Another RCT comparing PF preservation or re-attachment after standard posterior approach THA demonstrated significantly less muscle grade and bulk deterioration in the PF-preserving group at three postoperative months but no functional differences at two postoperative years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preserving soft tissue in BHA is important for reducing the risk of postoperative dislocation, and a variety of surgical approaches have been reported recently considering this complication [4]. The preservation technique of the piriformis tendon during the posterolateral approach in total hip arthroplasty (THA) is reportedly superior to the reattachment technique in terms of contiguity, muscle atrophy, and dislocation [5]. Kim et al reported a method of THA that preserves muscles from the piriformis muscle to the internal obturator muscle (external rotator preservation procedure [ERP]) and had good outcomes with no cases of postoperative dislocation [6].…”
Section: Introductionmentioning
confidence: 99%